Perbandingan sifat-sifat pentabletan Radix Glycyrrhizae dengan eksipien komersil secara pemampatan terus - Mohd Cairul Iqbal Mohd Amin,; Widianingsih, (penerbit ukm, 2005)
The objectives of this study were to investigate the physicochemical properties of Radix Glycyrrhizae as an excipient in tableting by using direct compression method and to compare it with other commercial excipients i.e. lactose, microcrystalline cellulose (MCC) and calcium lactate pentahydrate (Puracal). Particle sizes of all samples were limited to 200-250 μm. Scanning electron microscope showed that the particles of Radix Glycyrrhizae possessed a variety of uneven sizes and shapes similar to those of lactose whereas MCC particles were more needle-like structure while Puracal particles were more spherical and porous. The ability of all samples to be compressed, the true density of each sample particle, the effect of humidity on the stress relaxation of the samples and the porosity of the tablets were investigated. The bonding properties of the samples in tablet form were evaluated by measuring the tensile strength through diametral compression. The true densities of Radix Glycyrrhizae,lactose, MCC and Puracal were 1.5746, 1.5476, 1.6654 and 1.3506 g/cc, respectively. Radix Glycyrrhizae was found to have moderate compressibility and compactibility properties similar to lactose unlike Puracal and MCC which were far better compressed. The study on the effect of humidity on stress relaxation of the tablets showed that all samples were affected by changes in temperature. Heckel analysis on the samples suggested that Radix Glycyrrhizae showed plastic deformation properties similar to MCC while lactose and Puracal were of brittle fracture properties. In conclusion, Radix Glycyrrhizae could be compressed into tablet by using the direct compression method and its properties as an excipient was comparable to the other commercial excipients